Heterogeneous Solution NMR Signal Amplification by Reversible Exchange1. Issue 29 (30th May 2014) - Shi, Fan; Coffey, Aaron M.; Waddell, Kevin W.; Chekmenev, Eduard Y.; Goodson , Boyd M.
Abstract A novel variant of an iridium‐based organometallic catalyst was synthesized and used to enhance the NMR signals of pyridine in a heterogeneous phase by immobilization on polymer microbead solid supports. Upon administration of parahydrogen (pH2) gas to a methanol mixture containing the HET‐SABRE catalyst particles and the pyridine, up to fivefold enhancements were observed in the 1H NMR spectra after sample transfer to high field (9.4 T). Importantly, enhancements were not due to any residual catalyst molecules in solution, thus supporting the true heterogeneity of the SABRE process. Further significant improvements may be expected by systematic optimization of experimental parameters. Moreover, the heterogeneous catalyst is easy to separate and recycle, thus opening a door to future potential applications varying from spectroscopic studies of catalysis, to imaging metabolites in the body without concern of contamination from expensive and potentially toxic metal catalysts or accompanying organic molecules.